The use of a minimally invasive integrated endoscopic system to perform hemilaminectomies in chondrodystrophic dogs with thoracolumbar intervertebral disc extrusions - MacQuiddy, Brittany; Bartner, Lisa; Marolf, Angela; Rao, Sangeeta; Dupont, Emily; Adams, Taylor; Monnet, Eric (Frontiers in Veterinary Science, 2024)
The objective was to evaluate the use of a minimally invasive surgical (MIS) approach to perform hemilaminectomies in chondrodystrophic dogs with thoracolumbar intervertebral disc extrusions (IVDE). Additionally, we aimed to evaluate the degree of soft tissue trauma using the endoscopic procedure compared to the standard open approach. Eight client-owned dogs presented to the Colorado State University Veterinary Teaching Hospital with acute onset thoracolumbar IVDE were included in this study. This was a prospective, randomized case-series. Patients were assigned to undergo an endoscopic (group 1; n=4) or a standard open approach (group 2; n=4) for a hemilaminectomy. A post-operative MRI was performed in all cases. Conversion to an open approach was not necessary for any case in group 1. All cases had adequate spinal cord decompression on post-operative MRI. There was no significant difference in soft tissue changes noted on post-operative MRI between the two groups. The MIS approach to hemilaminectomies in chondrodystrophic dogs with thoracolumbar IVDE can successfully be performed to decompress the neural tissue and appears to lead to similar clinical outcomes in the early postoperative period compared to the standard open approach. Larger studies are needed to determine the potential advantages of the MIS technique compared to the standard open approach in veterinary medicine.